Towards Multi-Dimensional Adaptation of Digitised Historical Content - WADE, VINCENT PATRICK; LAWLESS, SEAMUS; O'CONNOR, ALEXANDER; CONLAN, OWEN; OHLMEYER, JANE; O SIOCHRU, MICHEAL; O'NEILL, ELEANOR (My University, 2011)
Traditional keyword-based search approaches are limited in their retrieval of digital content. In this paper we discuss progress towards multi-dimensional adaptation of digitised content in the context of the European Commission-funded CULTURA project. The supporting technology draws on adaptive hypermedia (AH) and adaptive web systems with the aim of enhancing user queries with contextual and user-specific information. Ultimately, the CULTURA project aims to provide a technological environment for the humanities, through which it becomes possible to address implicit questions that a researcher has not explicitly articulated. This is manifested in two particular aspects of CULTURA?s objectives. The first is in assisting the user in finding content that meets their needs and in discovering other content in which they will be interested. The second is to present that content in the context of other material with which the user is familiar, as well as supplemental resources and community generated commentary.
ACCEPTED
Keywords: Digital Humanities; Digitisation; CULTURA project